Autoclaves for Aerospace Applications: Issues and Challenges. (16th June 2011) - Upadhya, A. R.; Dayananda, G. N.; Kamalakannan, G. M.; Ramaswamy Setty, J.; Christopher Daniel, J.
Abstract : The Council of Scientific and Industerial Research National Aerospace Laboratories (CSIR-NAL), Bangalore, India has been engaged in the research of autoclaves for the past three decades and has pioneered their development and usage in India for aerospace/aircraft structural applications. The autoclaves at CSIR-NAL have played a significant role in all the major national aircraft/aerospace programs. The largest aerospace autoclave in India (working size of 4.4 m diameter and 9.0 m length) has been successfully commissioned at CSIR-NAL. This paper gives the technological challenges faced and the innovative concepts that were introduced in these autoclaves.